Tantangan Pendidikan Dasar Masa Depan Di Indonesia - Rizki Ananda; Adinda Regina; Herlianda Zahra; Marsela Aliati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The future of basic education in Indonesia is facing complex challenges, ranging from technological shifts and socio-economic inequalities to curriculum relevance and teacher capacity. This article explores these issues through a humanistic and reflective lens, emphasizing the importance of inclusive, adaptive, and student-centered approaches. It highlights the need for systemic transformation that is rooted in equity, innovation, and sustainable development to prepare Indonesian children for a rapidly changing world.